роль электрохиМичеСки активированных воДных раСтворов в коМплекСной терапии хроничеСкого пиелонеФрита - Н. А. Пахомова; Э. В. Минаков; К. М. Резников (Архивъ внутренней медицины)
In article importance of timely diagnostics and treatment of a chronic pyelonephritis is underlined. The text contains results of researches with using electrochemical activated water solutions in complex therapy of chronic pyelonephritis at a stationary and out-patient stage. These solutions can accelerate recovery and increase remission term at patients. Authors investigated a condition of free-radical oxidation and level antioxidant protection at patients with chronic pyelonephritis for studying mechanism of action electrochemical activated water solutions in the given pathology.